PENGARUH GAYA KEPEMIMPINAN TERHADAP PRESTASI KERJA KARYAWAN PADA DINAS PEKERJAAN UMUM KOTA MAGELANG - Sudiarto, Haryo; Koco, Bintaro (Universitas Muhammadiyah Magelang, 2006)
Leadership have the top-drawer role in forming condition and job environment which condusive to yield the good labour capacity as according to interest an organization. This researchtake the title ?Influence of Leadership Stylet to Labour Cpacity on Duty Public Work on Town Magelang?. Intention of this research is to know the influence of leadership style consisted of the autocratic leadership style, participative, and free rein to labour capacity by simultan and also parsial. Method of data collecting used in this research is method of observation and questionere. Population in this research is entire employees On Duty Public Work of Town Magelang while sampel used by as much 50 responden with the method in take of sample proportionale stratified where divisible population for leverr or strata. Pursuant to result of knowable examination F test taht any free variable of leadership style have the influence which significant by together or simultan to variable trussed by a labour capacity. This matteris proven with the result F calculate the > F Table that 37,375 > 2,4174. examination determinant coefficient or adjusted R square equal to 0,690 meaning that influence all free variable of leadership style to variable trussed by labour capacityequal 69% while the rest 0,310 or 31% influenced by other, dissimilar variable which do not covered in this research.